2020
DOI: 10.3847/1538-4357/ab659c
|View full text |Cite
|
Sign up to set email alerts
|

Implications from Late-time X-Ray Detections of Optically Selected Tidal Disruption Events: State Changes, Unification, and Detection Rates

Abstract: We present Chandra X-ray observations of four optically-selected tidal disruption events (TDEs) obtained 4-9 years after their discovery. Three sources were detected with luminosities between 9×10 40 and 3 × 10 42 erg s −1 . The spectrum of PTF09axc is consistent with a power law with index of 2.5±0.1, whereas the spectrum of PTF09ge is consistent with the Wien tail of a soft black body best described over the 0.3-7 keV range with a power law of index 3.9±0.5 (the best-fit black body temperature is 0.18 ± 0.02… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 127 publications
(183 reference statements)
10
78
0
Order By: Relevance
“…In RBS 1032 the spectrum after 20 years had hardened from Γ = 5 to Γ = 3.4 (Maksym et al 2014a). Interestingly, Jonker et al (2019) found late-time X-ray emission in three optically-selected TDEs. The spectra of these could be modeled with power-laws of Γ = 2.5−3.9, compatible with those of the X-ray selected events.…”
Section: Long-term Spectral Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In RBS 1032 the spectrum after 20 years had hardened from Γ = 5 to Γ = 3.4 (Maksym et al 2014a). Interestingly, Jonker et al (2019) found late-time X-ray emission in three optically-selected TDEs. The spectra of these could be modeled with power-laws of Γ = 2.5−3.9, compatible with those of the X-ray selected events.…”
Section: Long-term Spectral Evolutionmentioning
confidence: 99%
“…For reasons which are currently not well understood, optically and UV-bright TDEs tend to show little or no X-ray emission (Gezari et al 2009;Arcavi et al 2014;Jonker et al 2019, and see the Optical Chapter). Nevertheless there are some notable exceptions, two of which are examined below.…”
Section: X-ray Bright Events Discovered In Optical Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray spectral shape of these fast events is consistent with a power law (see the discussion and references in the contribution of Saxton et al to this Volume). This is in contrast to the early-time soft X-ray spectra typically found in TDEs involving more massive black holes and stars other than white dwarfs (for some references and a discussion on differences between earlyand late-time X-ray spectra of TDEs see for instance Jonker et al 2019). It seems unlikely that a difference in the (Eddington ratio) mass accretion rate in white dwarf and main-sequence TDEs is the main cause of the different spectral shape 2 .…”
Section: Fast X-ray Candidatesmentioning
confidence: 77%
“…Since power-law X-ray spectra are thought to be caused by Compton up-scattering of seed disc photons by a coronal electron population, which in turn is thought to be accelerated to relativistic energies in magnetic reconnection events (Merloni and Fabian 2001), a power-law spectrum may more naturally emerge in the TDE discs with large magnetisation such as those occurring in white dwarf disruptions. Note that a main-sequence/longer duration TDEs with hard power law like spectra are also more difficult to distinguish from AGN activity and therefore observers may be biased against classifying such events as TDEs (Jonker et al 2019).…”
Section: Fast X-ray Candidatesmentioning
confidence: 99%